Spheroidization heat treatment and intercritical annealing of low carbon steel - Nasiri Z.; Mirzadeh H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Spheroidization annealing of low carbon steel and its effects on the microstructure and mechanical properties of dual phase (DP) steel were studied. It was revealed that the reduction in strength and hardness of the quenched martensitic microstructure was much more pronounced compared to the fully annealed ferritic-pearlitic banded microstructure with spheroidizing time. This was related to the confinement of spheroidized carbide particles to distinct bands in the latter, and the uniform dispersion of carbides and high-temperature tempering of martensite in the former. During intercritical annealing of the spheroidized microstructures, the tendency to obtain martensite particles as discrete islands was observed. This, in turn, resulted in an inferior strength-ductility balance compared to the DP steel obtained from the intercritical annealing of martensite, which negated the usefulness of the spheroidized microstructures as the initial microstructures for the processing of DP steels.